The Media Language Of Sports Journalism And Its Role In Developing Some Social Values Of Algerian Youth - Abi , Mohammed; Bendkfal , Rachid (sports creativity, 2025)
The present study aims at recognizing the role of sport media’s journalisticlanguage in developping some social values among the Algerian youth. The descriptive method is used since it is more suitable. The case study involves several meadia channels like journalism, TV’s and radios. The study sample involves a hundred journalists that have been randomly chosen. The three chapters questionnaire ( media language, cooperation and objectivity) that is used results in the following: First, The media doesn’t change the youth’s values as it is thought to be, but it just complements the role of the basic educative institutions like family, school, primary groups and mosques. Second, Arabic is a keystone in enhancing journalism students’ skills and talents. Third, using the standard Arabic correctly as much as possible as a mean of communication in the media and shrinking the use of the dialects. Forth, Asking public authorities and researchers to pay attention about the importance of social values